The impact of AI-supported online classroom management (AIS-OCM) on attitudes toward english lessons, self-directed online learning, and academic achievement - Gocer, Sukran; Karabatak, Songul (Springer Heidelberg, 2026)
This study investigates the effects of AI-supported online classroom management (AIS-OCM) on students' attitudes toward English as a Foreign Language (EFL), their self-directed online learning skills, and academic achievement. The rapid development of digital technologies, particularly in the aftermath of the COVID-19 pandemic, has highlighted the need to sustain student engagement and motivation in online learning environments. Within this framework, AI-based tools and intelligent learning analytics systems offer promising potential for delivering personalized feedback and adaptive learning support. A quasi-experimental design was adopted, involving 7th-grade students from an EFL context. While the experimental group received AI-supported online instruction over eight weeks, the control group participated in standard online lessons without AI integration. Data were collected using pretest and posttest measures and analyzed with Mixed ANOVA to examine time, group, and time & times; group interaction effects focusing on attitudes toward EFL lessons, self-directed online learning, and academic performance. The findings indicate positive learning gains over time for both groups and generally more favorable outcomes for the AIS-OCM group, offering meaningful insights into the multidimensional impact of AIS-OCM. These results are expected to contribute to the growing body of research on AI-supported education and provide practical implications for educators and policymakers operating in EFL settings.
Keywords: AI-supported; Online classroom management; Self-directed online learning; EFL; Academic achievement; Student attitudes